The report of Chief of the General Staff of USSR marshal Alexander Jegorov about his visit in Lithuania, Latvia, and Estonia on 15th-26th of February, 1937 - Zenonas Butkus; Magnus llmjarv (Lietuvos Istorijos Studijos)
A. Jegorov's report to the People's Commissar of Defence Kliment Voroshilov that is being published has been found in the Russian State Military Archive (F. 33987. Ap. 3. B. 1035. L. 118-147). This report is a unique testimony of the USSR policy and international relations and a sign of the activity of the policy in question that in principle has never been used in scientific research. It raises doubts about the statement that has been and is still widely used in the works devoted to history, namely, that parceling out of the Baltic states in 1939 and their occupation in 1940 have been the actions provoked by the intricacies in the international situation and may not be directly associated with the preceding Soviet policy, which in general failed to be conceptual and well-planned and that at that time they received the given states not as a result of "their Baltic policy" but directly from "the hands of Berlin."